First report of Fusarium moniliforme causing cassava root and stem rot - Msikita, W.; Yaninek, John S.; Ahounou, M.; Fagbemissi, R. (Scientific Societies, 1996)
Fifty-five samples of diseased cassava (Manihot esculenta) crowns and shoots and discoloured chips were collected from Benin and Cameroon, Africa. Pieces of infected tissue were cultured on agar and incubated for a week. Over 36% of fungal isolates were Fusarium spp. Of the Fusarium isolates, 55% were from rotted roots and crowns of young and old plants and 45% were from chips. Over 44% of Fusarium isolates from the chips were F. moniliforme [Gibberella fujikuroi]. G. fujikuroi was reisolated from cassava with wilting and necrosis 6-10 d after inoculation. This is the first report of G. fujikuroi on cassava.